PENGOLAHAN AIR LIMBAH INDUSTRI KECIL PELAPISAN LOGAM - Yudo, Satmoko; Said, Nusa Idaman (Jurnal Air Indonesia, 2005)
Water pollution in Jakarta area, especially river and shallow groundwater, had become a very serious problem. Pollution problem caused by small industrial activities had not been got attetion. Some activities, which often cause water pollution problem, were wastewater from electroplating small industry. This wastewater was one of the most potential pollutant sources, because it contains high concentration of heavy metal pollutant such as Fe, Ni, Zn, Cr, ect. To anticipate its negative effect to the environment and social life, it needs to provide a technical standard plan to manage wastewater treatment plant, especially of electroplating small industries. The purpose of these activities is to do the assessment and application of wastewater treatment technology of electroplating small industry. The target is to get design engineering and pilot plant of wastewater treatment technology for electroplating small industry.Ã‚Â Kata kunci : Pencemaran logam berat, Pengolahan limbah cair industri kecil pelapisan logam.